FORENSICALLY IMPORTANT BLOW FLIES (DIPTERA: CALLIPHORIDAE) OF PUNJAB (INDIA) - SINGH, DEVINDER; BHARTI, MEENAKSHI (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2000)
Various species of blow flies are used as forensic indicators during crime investigation in different parts of the world. Sufficient data in still not available about family Caliphoridae in India so that they can be put to forensic use in our country as well. Preliminary information is provided about the species available in the state of Punjab along with notes from literature about their use in forensic entomology.